Preventing child abuse and neglect - Vildan Cirik; Sule Ciftcioglu; Emine Efe (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Aim: To inform about the prevention of child abuse and neglect. Method: This study was prepared as a compilation. The studies published between 2000 and 2017 were reviewed, researchers searched the keywords of "child abuse, child neglect, prevention, nurse" in Turkish and English on the international "PubMed", "Embase", "Ovid", "ProQuest", "Ebscohost" and national Turkish Medical Index. Results: Effective programmes are those that support parents and teach positive parenting skills. Some of the most effective responses for preventing child abuse and neglect focus on child-rearing, parentchild relationships and the family environment, including training in parenting. Nurses have a key role to play in identifying, treating and referring cases of abuse and neglect as well as reporting suspected cases of maltreatment to the appropriate authorities. Conclusion: Child abuse and neglect have a long-lasting impact on the child, their family and the following generations. In order to protect children from this situation, it is necessary to develop preventive programs and to develope and inforce legal ramifi cations. Recommendations/future directions: Additional research and training is needed to determine effective approaches for nurses to prevent child abuse or neglect.